Endovascular Treatment of Chronic and Acute on Chronic Mesenteric Ischaemia: Results From a National Cohort of 245 Cases. (April 2021) - Altintas, Ümit; Lawaetz, Martin; de la Motte, Louise; Riazi, Hadi; Lönn, Lars; Lindh, Mats; Sillesen, Henrik; Eiberg, Jonas
Abstract : Objective: Endovascular treatment of chronic mesenteric ischaemia (CMI) is linked to low early morbidity and mortality but a higher risk of recurrence than open repair. Mid and long term outcomes after endovascular treatment remain to be proven in larger series. The aim of this study was to assess short and mid term outcome after first line endovascular revascularisation of CMI and acute on chronic mesenteric ischaemia (AoCMI). Methods: This was a prospective population and registry based cohort study supplemented by a retrospective review of medical records and imaging files. A national cohort was created based on data extracted from the Danish National Registry for Vascular Surgery (Karbase) for all patients treated endovascularly for CMI or AoCMI between 2011 and 2015 in Denmark. Survival data, bowel resection, complications, re-intervention rate, and improvement of clinical symptoms were analysed, as were potential risk factors. Results: In total, 245 patients had an endovascular intervention for CMI ( n  = 178; 72.6%) and AoCMI ( n  = 67; 27.3%). One and three year survival estimates were 85% (95% confidence interval [CI] 79 – 90) and 74% (95% CI 67 – 80) in the CMI-group, and 67% (95% CI 54 – 77) and 54% (95% CI 41 – 65) in the AoCMI group. The hazard ratio for death was 1.89 (95% CI 1.23 – 2.9) for AoCMI, relative to patients with CMI. Superior mesenteric artery (SMA) stenosis, rather then occlusion, significantly increased the success of SMA recanalisation: OR 19.4 (95% CI 6.2 – 61.4) and 9.3 (95% CI 1.6 – 53.6) in the CMI and AoCMI groups, respectively. The proportion of patients reporting clinical improvement was 71% ( n  = 127) in the CMI group and 59% ( n  = 39) in the AoCMI group. Five patients (3%) in the CMI and 30 (45%) in the AoCMI groups underwent bowel resection (p < .001), and the overall length of hospital stay (LoS) was a median of two days (interquartile range [IQR] 1 – 3 days) in the CMI group and seven days (IQR 3 – 23 days) in the AoCMI group. Within the first year, re-intervention was performed in 14 patients (5.7%). Conclusion: First line endovascular treatment of CMI carries a three year mortality rate of 25%, and low risk of re-occurrence of symptomatic ischaemia. Relative to CMI, patients suffering AoCMI have significantly higher morbidity and mortality, more bowel resections, and longer LoS.